2015
DOI: 10.1038/ncomms8117
|View full text |Cite
|
Sign up to set email alerts
|

Chirality transfer from gold nanocluster to adsorbate evidenced by vibrational circular dichroism

Abstract: The transfer of chirality from one set of molecules to another is fundamental for applications in chiral technology and has likely played a crucial role for establishing homochirality on earth. Here we show that an intrinsically chiral gold cluster can transfer its handedness to an achiral molecule adsorbed on its surface. Solutions of chiral Au38(2-PET)24 (2-PET=2-phenylethylthiolate) cluster enantiomers show strong vibrational circular dichroism (VCD) signals in vibrations of the achiral adsorbate. Density f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
142
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(145 citation statements)
references
References 38 publications
(45 reference statements)
2
142
0
1
Order By: Relevance
“…The model ligands -SH should lead to higher symmetries in the clusters, since only the symmetry of the Au-S framework and the relative orientation of the ligands with respect to the protecting Au-Soligomers are considered. Certain conformations of actual ligands (such as -SCH 2 CH 2 Ph) may yield the symmetry of the clusters, as demonstrated in recent experimental and theoretical work 65,66. The effect of the ligands itself on the molecular symmetry is best demonstrated by comparing the [Au25 (SCH 2 CH 2 Ph)18 ] -cluster with[Au 25 (capt) …”
mentioning
confidence: 92%
“…The model ligands -SH should lead to higher symmetries in the clusters, since only the symmetry of the Au-S framework and the relative orientation of the ligands with respect to the protecting Au-Soligomers are considered. Certain conformations of actual ligands (such as -SCH 2 CH 2 Ph) may yield the symmetry of the clusters, as demonstrated in recent experimental and theoretical work 65,66. The effect of the ligands itself on the molecular symmetry is best demonstrated by comparing the [Au25 (SCH 2 CH 2 Ph)18 ] -cluster with[Au 25 (capt) …”
mentioning
confidence: 92%
“…[78] The handedness of chiral gold nanocluster can be "transferred" to its adsorbate achiral molecule, and Figure 3c is the schematic of Au 38 (2PET) 24 nanocluster. [79] In this ensemble, the interaction between achiral molecules and chiral gold nanostructure broke the mirror symmetry, resulting in the chirality of molecules.…”
Section: Chiral Interactionsmentioning
confidence: 99%
“…Reproduced with permission. [79] Copyright 2015, Nature Publishing Group. d) Schematic of the coupling effect between chiral molecule and plasmonic dimer.…”
Section: Quasi-2d Periodic Chiral Nanostructuresmentioning
confidence: 99%
“…[1] Unlike the extensively studied molecular chirality [2] and that of the microscopic helix, [3] the nanoscale chirality between them remains largely uninvestigated. It is suggested that atomically precise chiral Au nanoclusters [6] would become an ideal platform at the nanoscale for understanding the chiral transfer across the organic-inorganic interface [7] and structure-property relationships. It is suggested that atomically precise chiral Au nanoclusters [6] would become an ideal platform at the nanoscale for understanding the chiral transfer across the organic-inorganic interface [7] and structure-property relationships.…”
mentioning
confidence: 99%
“…[4] Although significant advances have been achieved in this field, [5] the chiral evolution from molecules to nanostructures, as well as the corresponding influence on their properties are not clearly elucidated yet. It is suggested that atomically precise chiral Au nanoclusters [6] would become an ideal platform at the nanoscale for understanding the chiral transfer across the organic-inorganic interface [7] and structure-property relationships. [8] Among chiral Au nanoclusters,A u 20 is of special interest owing to its intrinsic chiral core,w hich is quite distinct from other clusters in which the chirality has other origins.Indetail, the atomic structure of Au 20 core is ac entered icosahedral Au 13 unit surrounded by ahelical arrangement of Au 7 fan-like motif ( Figure S1 in the Supporting Information).…”
mentioning
confidence: 99%